Caracterização de antígenos imunodominantes de Pythium insidiosum reconhecidos por anticorpos de eqüinos, coelhos e bovinos - Cavalheiro, Patrícia Bernardes (2010)
Oomycete Pythium insisiosum is the etiologic agent of pythiosis, chronic and granulomatous disease, which affects humans and animals in tropical and subtropical areas of the world. Due to ergosterol absence in the plasmatic membrane of this microorganism, treatments based on antifungal agents have been ineffective. Immunotherapy has emerged showing promising results. In this context, the improvement of the immunotherapy was the main goal of this study, whose first purpose was to characterize the immunodominant antigens from this species (P. insidosum ATCC 58637 and P. insidiosum 210-LAPEMI) through sodium dodecyl sulfate polyacrylamide gel eletrophoresis (SDS-PAGE). Some proteins showing 15 kDa to 120 kDa were detected, and bands were transferred to nitrocellulose membranes in order to develop the western blot tests. The second purpose was to characterize the humoral response to pythiosis in equine, in bovine and in experimental pythiosis in rabbits, considering the no treated disease, the disease cured by immunotherapy, the disease treated with immunotherapy but not cured, and the disease cured spontaneously. To encompass all these cases we have included sera from: a) horses cured by immunotherapy; b) horses with pythiosis but not responsive to immunotherapy; c) horses with pythiosis but not treated; d) bovines with pythiosis and showing spontaneous cure; e) rabbits with experimental pythiosis but not treated; and f) rabbits with experimental pythiosis treated with immunotherapy. All specimens recognized three immunodominant proteins: 74, 33 and 32 kDa. The sera from horses cured by immunotherapy (a) and bovine sera (d) recognized another immunodominant protein, 55 kDa, which was weakly positive or negative in the other groups. Thus, the 74, 33 and 32 kDa immunodominant proteins suggest a relevant function in the humoral response to pythiosis because they were recognized by horses, rabbits and bovines. In addition, the 55 kDa antigen, which is being reported here for the first time, is likely to be involved in the cure mechanisms stimulated by immunotherapy.